2017
DOI: 10.1139/gen-2016-0017
|View full text |Cite
|
Sign up to set email alerts
|

Mapping QTLs associated with agronomic and physiological traits under terminal drought and heat stress conditions in wheat (Triticum aestivum L.)

Abstract: Wheat crops frequently experience a combination of abiotic stresses in the field, but most quantitative trait loci (QTL) studies have focused on the identification of QTLs for traits under single stress field conditions. A recombinant inbred line (RIL) population derived from SeriM82 × Babax was used to map QTLs under well-irrigated, heat, drought, and a combination of heat and drought stress conditions in two years. A total of 477 DNA markers were used to construct linkage groups that covered 1619.6 cM of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
77
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(88 citation statements)
references
References 74 publications
10
77
1
Order By: Relevance
“…Another study had previously reported many MTAs on chromosome 1A detected for yield components under heat stress, but all were found to have a pleiotropic relationship with days to heading and were also located on the short arm of 1A [26], instead of 1AL found here. A heat-specific QTL was also detected on the same chromosome in the short arm for spikelet compactness and leaf rolling in bread wheat [76]. An earlier study identified a QTL on 1AS for yield but associated with different stress conditions [77].…”
Section: Dissection Of Heat-specific Qtls Associated With Yield-relatmentioning
confidence: 81%
See 1 more Smart Citation
“…Another study had previously reported many MTAs on chromosome 1A detected for yield components under heat stress, but all were found to have a pleiotropic relationship with days to heading and were also located on the short arm of 1A [26], instead of 1AL found here. A heat-specific QTL was also detected on the same chromosome in the short arm for spikelet compactness and leaf rolling in bread wheat [76]. An earlier study identified a QTL on 1AS for yield but associated with different stress conditions [77].…”
Section: Dissection Of Heat-specific Qtls Associated With Yield-relatmentioning
confidence: 81%
“…The second major QTL region was detected on the long arm of chromosome 5B and found to be associated with GNSpk and the two indices SSI-GY and TOL-GY, contributing to 37% of the phenotypic variation. A region in the short arm of the same chromosome has been previously reported to be associated with grain number per square meter in bread wheat [76], and controlling thousand grain weight in durum wheat [27] under combined drought and heat stress. Shirdelmoghanloo et al [25] and Acuna-Galindo et al [78] reported loci for grain weight and other important traits on chromosome 5B under heat and non-heat conditions in hexaploid wheat.…”
Section: Dissection Of Heat-specific Qtls Associated With Yield-relatmentioning
confidence: 99%
“…However, previous QTL studies conducted in wheat also identified QTLs for leaf chlorophyll content under heat stress on other chromosomes including 1B, 1D, 6A, and 7A ( Talukder et al, 2014 ), which were not detected at the seedling stage in the current study. Moreover, in another QTL study, leaf chlorophyll content QTLs under heat stress mapped on chromosomes 1A and 6B were reported ( Tahmasebi et al, 2016 ). Again, these QTLs were not detected in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Then, genetic data can be linked with phenotypic data to identify the QTLs/genes associated with physiological traits that directly or indirectly affect the plant tolerance to water deficit and heat stress [2,83,84]. Identifying QTLs associated with CMS using association mapping requires large populations to increase the recombination frequency and the frequency of rare alleles [19].…”
Section: Association Mappingmentioning
confidence: 99%
“…The urgent need to increase global wheat production requires greater progress in improving wheat tolerance to biotic and abiotic stresses. Terminal drought and heat are two major abiotic stresses that frequently coexist in wheat [1,2], causing deleterious effects on many biochemical and physiological processes, including disruption of cell membrane stability. Drought tolerance mechanisms can be classified into three broad categories such as drought escape, drought avoidance, and biochemical tolerance of the tissue to water deficit [3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%